Field Of Dreams - O'Neill, Peggy (Utah State University Press, 2003)
One of the first collections to focus on independent writing programs, A Field of Dreams offers a complex picture of the experience of the stand-alone. Included here are narratives of individual programs from a wide range of institutions, exploring such issues as what institutional issues led to their independence, how independence solved or created administrative problems, how it changed the culture of the writing program and faculty sense of purpose, success, or failure. Further chapters build larger ideas about the advantages and disadvantages of stand-alone status, covering labor issues, promotion/tenure issues, institutional politics, and others. A retrospective on the famous controversy at Minnesota is included, along with a look at the long-established independent programs at Harvard and Syracuse. Finally, the book considers disciplinary questions raised by the growth of stand-alone programs. Authors here respond with critique and reflection to ideas raised by other chapters-do current independent models inadvertently diminish the influence of rhetoric and composition scholarship? Do they tend to ignore the outward movement of literacy toward technology? Can they be structured to enhance interdisciplinary or writing-across-the-curriculum efforts? Can independent programs play a more influential role in the university than they do from the English department?